Aluminum-powered climate change resiliency: From aluminum debris to electricity and clean water. (1st October 2020) - Godart, Peter; Hart, Douglas
Highlights: Aluminum debris is highly energy dense can be treated to rapidly oxidize in water. The aluminum-water reaction produces hydrogen gas, aluminum oxyhydroxide, and heat. Treated aluminum debris can be used to generate electricity at the kilowatt scale. The heat from the aluminum-water reaction can power seawater desalination. The electricity, water, and aluminum oxyhydroxide value exceeds scrap price by 600%. Abstract: This paper presents a novel ecosystem for converting aluminum debris from a natural disaster to a stable water-reactive fuel that can be used to generate electricity and power emergency desalination. Bulk aluminum can be made water-reactive via a minimal surface treatment of gallium and indium, which works to passivate the oxide layer that would otherwise inhibit the reaction. With this oxide layer disrupted, the underlying bulk aluminum is able to react exothermically with water to produce hydrogen gas and aluminum oxyhydroxide (AlO(OH)) at high levels of reaction completion (>95%). The gallium and indium, which are not consumed in the initial reaction, can be recycled to produce more fuel. Several systems for converting the hydrogen product of this reaction to electricity are reviewed here, as well as a device capable of desalinating seawater using the thermal energy released in the aluminum-water reaction to drive a reverse osmosis process. Finally, a new economics analysis of the value of the electricity, water, and AlO(OH) outputs of this system was performed for 10 different countries and territories. In each case this value is shown to outweigh the scrap price of aluminum by up to 600%, providing added economic incentive for utilizing this aluminum treatment process as a means of post-disaster cleanup and subsequent disaster preparedness.